Partisipasi Politik Masyarakat Pada Pemilihan Kepala Desa Di Desa Cinta Rakyat Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Helen Meliana R Hutajulu; Angelina Putri; Julia Ivanna (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research article describes community participation in the village head election in Cinta Rakyat Village. The problem in this research is the problem of human resources who do not yet have awareness in politics which has an impact on political participation rates. The type of research used by the researcher is qualitative research and in collecting data the researcher carried out direct observations, using interview techniques and documentation studies. Based on this research, it can be illustrated that community participation in the election of village heads in Kampungsawah Village, Percut Sei Tuan District, Deli Serdang Regency is still very low, seen from the indicators discovered by Ramlah Surbakti, namely: 1) Political awareness. 2) Trust in the government. 3) Socioeconomic status. The reason for the low political participation rate in this research is due to a lack of political awareness so that many people are reluctant to vote if there are no village head.